Solutions To Entrepreneurship Problems: Optimization Of Entrepreneurship Education In College Education - Khoiri Mustafa; Suyadi Suyadi (At-Tarbiyat, 2021)
Entrepreneurship, considered an essential element of economic and social growth worldwide, is one of the most developing research fields in academia. Entrepreneurship can increase national competitiveness and promote economic growth by creating jobs and bringing innovation to business. Therefore countries want to increase the level of entrepreneurship to promote economic and social development. The empowerment of entrepreneurship is very strategic because of its great potential in driving people’s economic activities and, at the same time, being the source of income for most people in improving their welfare. Giving awareness about the importance of entrepreneurship is very important to do especially in universities.